Sustained intrathecal delivery of amphotericin B using an injectable and biodegradable thermogel - Wenting Lin (Drug Delivery, 2021)
Cryptococcal meningitis is a fungal infectious disease with a poor prognosis and high mortality. Amphotericin B (AMB) is the first choice for the treatment of cryptococcal meninges. The blood-brain barrier (BBB) is the major barrier for the effective delivery of drugs to the brain. In this study, AMB was incorporated in a thermosensitive gel for intrathecal injection. We first synthesized AMB-loaded thermogel, investigated its in vitro cumulative release, and in vivo neurotoxicity, and therapeutic effect. The thermosensitive gel was comprised of 25 wt% poly (lactic acid-co-glycolic acid)-poly (ethylene glycol)-poly (lactic acid-co-glycolic acid) (PLGA-PEG-PLGA) triblock polymer aqueous solution. The AMB loaded in the thermosensitive gel (AMB in gel) had low viscosity at low temperature and resulted in the formation of a non-flowing gel at 37 °C (physiological temperature). AMB loading in gel sustained its release for 36 days and the in vitro cumulative release rate was satisfactory. Compared with the AMB solution, intrathecal administration of AMB in gel could reduce the neurovirulence of AMB and get a better treatment effect. The findings of the current study show that the injectable PLGA–PEG–PLGA thermogel is a biocompatible carrier for the delivery of drugs into the intrathecal.